Think Pair Share Method as a Tool to Increase Student Interest and Learning Outcomes - Fernández, Meléndez; Quintana, Jacob; Dominic, Walker; Darius, Liu; Alexandra, White (World Psychology, 2022)
Given the development of learning in this day and age, many schools are using the Think Pair Share type cooperative learning method. Therefore, researchers conducted a study, to see the development of increasing student interest and learning outcomes in using the Think Pair Share method. The type of research conducted by researchers is a quantitative research method with a survey model and in-depth interviews. The results of this study, the Think Pair Share method, can increase students to think and respond. It is a factor of increasing a student's knowledge or ability to respond to questions and increasing the growing sense of helping each other, for example in doing group work. The conclusion of this research is that after applying the coorparative method of Think Pair Share type, the level of cooperation and knowledge of students has increased, but there are still some students who have not experienced an increase in terms of interest or learning outcomes. The limitation of this researcher is that researchers have not been able to find ways to overcome students who have not improved in terms of interest or learning outcomes, therefore researchers hope that future researchers can find ways to overcome students who have not improved